Optimizing Reading Comprehension Through Authentic Texts to Seventh-Grade Learners - Alya Melinda; Luthfiyatun Thoyyibah; Etika Rachmawati (Journal of English Education Program (JEEP), 2026)
Reading comprehension is a vital component of English as a Foreign Language (EFL) learning, yet Indonesian junior high school students often struggle due to limited exposure to authentic language use. Traditional textbooks, while aligned with curriculum standards, frequently lack contextual richness, reducing engagement and comprehension. Although previous research underscores the benefits of authentic materials, most studies emphasize digital resources or quantitative outcomes, with little exploration of classroom processes in rural, resource-limited contexts. This study investigated the impact of printed authentic texts specifically brochures and restaurant menus on the reading comprehension of seventh-grade students in Ciamis, Indonesia, and examined the strategies and challenges in their implementation. Using a qualitative case study design, data were collected through classroom observations, semi-structured interviews, and document analysis involving one English teacher and six students of varying proficiency levels. Thematic analysis revealed that authentic texts enhanced engagement, contextualized vocabulary learning, and encouraged collaborative meaning-making. Challenges included unfamiliar vocabulary, idiomatic expressions, varying proficiency levels, and time constraints, which required scaffolding strategies such as pre-teaching vocabulary, segmenting texts, using visual aids, and fostering peer support. The findings suggest that printed authentic materials, when culturally and linguistically adapted and paired with effective instructional scaffolding, can significantly improve reading comprehension and motivation, making them a valuable tool for student-centered EFL instruction in similar educational contexts.